EDUKASI PEMILIHAN BALUTAN MENINGKATKAN KEMAMPUAN PRAKTIK PERAWATAN LUKA DALAM KEGIATAN HOME CARE BAGI ALUMNI PRODI KEPERAWATAN BATURAJA - Ni Ketut Sujati; Nelly Rustiati; Supangat Supangat; M. Agung Akbar (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
The demand for home nursing care services, namely medical surgical cases, is increasing along with the variety of cases being treated by the client's family. The increase in cases requiring home care is a practice opportunity for nurses. Several alumni of the Baturaja Nursing Study Program have experienced problems in the choice of dressings in the practice of modern wound nursing care with a balanced moist concept. training with the TANDUR approach improves the ability of nurses in the practice of wound nursing care. The purpose of this community service is that the Alumni Nurses of the Baturaja Nursing Study Program are able to practice the selection of appropriate dressings to ensure a balanced moist atmosphere in the practice of wound nursing care. Community service activities with the Community Partnership Program scheme with a target audience of alumni, Nurses are given education through Zoom how to choose a balanced moist dressing for wound care practices at the client's home. Furthermore, the evaluation of practical ability is carried out via WhatsApp. The results obtained are that the education given to nurses increases the ability to practice dressing selection according to the moist balance method. In conclusion, this educational activity is very useful by providing training on choosing the right wound dressing.